2015
DOI: 10.1080/07362994.2015.1014102
|View full text |Cite
|
Sign up to set email alerts
|

Weak Euler Approximation for Itô Diffusion and Jump Processes

Abstract: This article studies the rate of convergence of the weak Euler approximation for Itô diffusion and jump processes with Hölder-continuous generators. It covers a number of stochastic processes including the nondegenerate diffusion processes and a class of stochastic differential equations driven by stable processes. To estimate the rate of convergence, the existence of a unique solution to the corresponding backwardKolmogorov equation in Hölder space is first proved. It then shows that the Euler scheme yields p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Our approach permits to establish that this bound holds true, up to an additional slowly varying factor in the exponent, for the difference of the densities itself, which again corresponds to the weak error (1.3) for a δ-function. We also mention the recent work of Mikulevičius et al [Mik12], [MZ15], concerning some extensions of [MP91] to jump-driven SDEs with Hölder coefficients.…”
mentioning
confidence: 95%
“…Our approach permits to establish that this bound holds true, up to an additional slowly varying factor in the exponent, for the difference of the densities itself, which again corresponds to the weak error (1.3) for a δ-function. We also mention the recent work of Mikulevičius et al [Mik12], [MZ15], concerning some extensions of [MP91] to jump-driven SDEs with Hölder coefficients.…”
mentioning
confidence: 95%
“…Using the regularity of the solution of the PDE ∂ t u = Lu with u(0, x) = f (x) where L is the infinitesimal generator of X with coefficients in some Hölder space and F a class of Hölder continuous functions, the weak rate of convergence was given in R. Mikulevičius and E. Platen [37] and R. Mikulevičius and C. Zhang [36]. More precisely, if for α ∈ (2, 3).…”
Section: Introductionmentioning
confidence: 99%
“…∈ C 4 (R , R )) to achieve a rate 1 [49]. In [38,39], it is shown that for -Hölder continuous coefficients with < 2, the order of convergence is /2. This approach excludes the integer values of , and the terminal condition is required to be (2+ )-Hölder continuous.…”
Section: Remarkmentioning
confidence: 99%